Recombinant activated factor VII does not reduce bleeding in rabbits treated with aspirin and clopidogrel - Hindy-François, Clemence; Bachelot-Loza, Christilla; Bonniec, Bernard Le; Grelac, Francoise; Dizier, Blandine; Godier, Anne; Emmerich, Joseph; Gaussem, Pascale; Samama, Charles-Marc (Thrombosis and Haemostasis, 2010)
Combined antiplatelet agents (cAPA), aspirin plus clopidogrel, increase the risk of bleeding. We hypothesised that recombinant activated FVIIa (rFVIIa), which normalises thrombin generation in platelet-rich plasma from patients treated with cAPA, could limit this bleeding risk. It was the objective of this study to investigate the efficacy and safety of rFVIIa compared to placebo, in a bleeding and thrombosis model in rabbits treated with aspirin and clopidogrel. New-Zealand rabbits, randomised into two groups (Placebo1, n=36 ; cAPA, n=34), were anaesthetised, ventilated and monitored for blood pressure, temperature and carotid blood flow. The Folts model was applied to a carotid artery. Cyclic flow reductions (CFR) were recorded over a first 20-min period (Obs1). Each rabbit was then randomly assigned into one of three subgroups (Placebo2, 40 μg/kg rFVIIa, 160 μg/kg rFVIIa) and CFR were monitored for a second 20-min period (Obs2). Ear bleeding time (BT) was measured at the end of each period. Hepatosplenic (HS) section was performed at the end of the experiment and HS blood loss defines the primary endpoint. Secondary endpoints were thrombosis (CFR), prothrombin time, platelet aggregation, and thrombin generation. Non- parametric statistical tests were used (p<0.05). cAPA significantly increased HS blood loss, BT and suppressed CFR compared to Placebo1 (p<0.05). rFVIIa injection did not modify HS blood loss, BT or CFR rate in Placebo1 rabbits nor in cAPA animals. These effects were unaffected by either rFVIIa dose. rFVIIa accelerated thrombin generation but had no effect on platelet aggregation in citrated platelet-rich plasma. rFVIIa did not modify HS blood loss associated with cAPA in rabbits.
Keywords: Aspirin; bleeding; clopidogrel; rFVIIa; thrombosis; rabbit